Kynurenine serves as useful biomarker in acute, Long- and Post-COVID-19 diagnostics - Bizjak, Daniel Alexander; Stangl, Manfred; Börner, Nikolaus; Bösch, Florian; Durner, Joachim; Drunin, Gergana; Buhl, Jasmine-Leonike; Abendroth, Dietmar (Frontiers in Immunology, 2022)
Introduction: In patients with SARS-CoV-2, innate immunity is playing a central role, depicted by hyperinflammation and longer lasting inflammatory response. Reliable inflammatory markers that cover both acute and long-lasting COVID-19 monitoring are still lacking. Thus, we investigated one specific inflammatory marker involved as one key player of the immune system, kynurenine (Kyn), and its use for diagnosis/detection of the Long-/Post-COVID syndrome in comparison to currently used markers in both serum and saliva samples. Material and Methods: The study compromised in total 151 inpatients with a SARS-CoV-2 infection hospitalized between 03/2020 and 09/2021. The group NC (normal controls) included blood bank donors (n=302, 144f/158m, mean age 47.1 ± 18.3 years (range 18-75)). Two further groups were generated based on Group A (n=85, 27f/58m, mean age 63.1 ± 18.3 years (range 19-90), acute admission to the hospital) and Group B (n=66, 22f/44m, mean age 66.6 ± 17.6 years (range 17-90), admitted either for weaning or for rehabilitation period due to Long-COVID symptoms /syndrome). Plasma concentrations of Kyn, C-Reactive Protein (CRP) and interleukin-6 (IL-6) were measured on admission. In Group B we determined Kyn 4 weeks after the negative PCR-test. In a subset of patients (n=11) concentrations of Kyn and CRP were measured in sera and saliva two, three and four months after dismission. We identified 12 patients with Post-COVID symptoms >20 weeks with still significant elevated Kyn-levels. Results: Mean values for NC used as reference were 2.79 ± 0.61 µM, range 1.2-4.1 µM. On admission, patients showed significantly higher concentrations of Kyn compared to NC (p-values < 0.001). Kyn significantly correlated with IL-6 peak-values (r=0.411; p-values <0.001) and CRP (r=0.488, p-values<0.001). Kyn values in Group B (Long-/Post-COVID) showed still significant higher values (8.77 ± 1.72 µM, range 5.5-16.6 µM), whereas CRP values in Group B were in the normal range. Conclusion: Serum and saliva Kyn are reflecting the acute and long-term pathophysiology of the SARS-CoV-2 disease concerning the innate immune response and thus may serve a useful biomarker for diagnosis and monitoring both Long- and Post-COVID syndrome and its therapy.